Revue theater dissected: a dialogue between France and Brazil (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This critical review presents to the academic community and others interested in revue theater the study by Professor Romain Piana (Université Sorbonne Nouvelle - Paris 3), published in November 2024. In his book, the author carefully examines the French theatrical genre, detailing its main structural, dramaturgical, and scenic characteristics, while emphasizing the intrinsic link between revue theater and what Piana (2024) calls the “media era.” Given the strong impact of the revue in Brazil, Piana’s study stands out as a qualified reference that not only deepens the understanding of the theatrical genre, but also encourages dialogue between the French and Brazilian traditions.
Keywords: revue theater; brazilian theater; french theater